Young athletes: Preventing sudden death by adopting a modern screening approach? A critical review and the opening of a debate. (June 2021) - Angelini, Paolo; Muthupillai, Raja; Lopez, Alberto; Cheong, Benjamin; Uribe, Carlo; Hernandez, Eduardo; Coulter, Stephanie; Perin, Emerson; Molossi, Silvana; Gentile, Federico; Flamm, Scott; Lorenz, Giovanni; et al.
Highlights: Sudden cardiac death (SCD), especially in young athletes, should be avoided. Current pre-sports screening is based on history/physical exam (insufficient). ECG is an excellent test for electrically induced SCD but requires expert review. Screening MRI is the best tool for identifying myocardiopathies/coronary anomalies. Results of a preliminary population-based study confirm the value of screening MRI. Abstract: Preventing sudden cardiac death (SCD) in athletes is a primary duty of sports cardiologists. Current recommendations for detecting high-risk cardiovascular conditions (hr-CVCs) are history and physical examination (H&P)-based. We discuss the effectiveness of H&P-based screening versus more-modern and accurate methods. In this position paper, we review current authoritative statements and suggest a novel alternative: screening MRI (s-MRI), supported by evidence from a preliminary population-based study (completed in 2018), and a prospective, controlled study in military recruits (in development). We present: 1. Literature-Based Comparisons (for diagnosing hr-CVCs): Two recent studies using traditional methods to identify hr-CVCs in >3, 000 young athletes are compared with our s-MRI-based study of 5, 169 adolescents. 2. Critical Review of Previous Results: The reported incidence of SCD in athletes is presently based on retrospective, observational, and incomplete studies. H&P's screening value seems minimal for structural heart disease, versus echocardiography (which improves diagnosis for high-risk cardiomyopathies) and s-MRI (which also identifies high-risk coronary artery anomalies). Electrocardiography is valuable in screening for potentially high-risk electrophysiological anomalies. 3. Proposed Project : We propose a prospective, controlled study (2 comparable large cohorts: one historical, one prospective) to compare: (1) diagnostic accuracy and resulting mortality-prevention performance of traditional screening methods versus questionnaire/electrocardiography/s-MRI, during 2-month periods of intense, structured exercise (in military recruits, in advanced state of preparation); (2) global costs and cost/efficiency between these two methods. This study should contribute significantly toward a comprehensive understanding of the incidence and causes of exercise-related mortality (including establishing a definition of hr-CVCs) while aiming to reduce mortality.